The Persistence of Hunting and Gathering Economies - Svizzero, Serge; Tisdell, Clem (Izdatel'skii Dom Uchitel', 2015)
After agriculture commenced ten thousand years ago, hunting and gathering economies are supposed to have shrunk rapidly, almost vanishing except in areas unsuitable for cultivation. We demonstrate that, even after the diffusion of agropastoralism, some of these economies persisted until recent times and some even survive nowadays. We develop three main arguments. First, foraging should be viewed as a possible optimal alternative to farming. Second, some foragers were involved into a dual economy in which they traded with farmers. Moreover, food procurement (gathering and hunting) and food production were combined by some groups of people. While these mixed-economies are often perceived as a necessary but temporary and an unstable stage in cultural evolution, in some cases, they proved to be a stable end-point or to be sustained for a very long time. Third, it is argued that some hunter-gatherers did not adopt agriculture owing to their values, beliefs and institutions.